Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Selama Pembelajaran Jarak Jauh Di Raudhatul Athfal - Restu Pujianti; Sumardi Sumardi; Sima Mulyadi (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2021)
Children’s social emotional development is the child’s achievement in adjusting to his environment and understanding his feelings when interacting with others. This emotional social development can develop one of which is through learning activities in schools where children learn various things and interact with many people, especially peers. There are three indicators of the achievement of social emotional development in early childhood, namely self-awareness, a sense of responsibility for oneself and others, and prosocial behavior. In this article, the author describe the social emotional development of children aged 5-6 years during distance learning at Raudhatul Athfal in Cipedes District, Tasikmalaya City. The research method used in this research is descriptive quantitative using a survey across sectional research desain, namely data collection is carried out at one time.